Financial development and minimum capital requirements in macroeconomic analysis - Miho Sunaga (Osaka University, Institute of Social and Economic Research (ISER), 2023)
We develop a macroeconomic model with a moral hazard problem between financial intermediaries and households, which causes inefficient resource allocation, to make us reconsider the financial regulation according to financial development, and individual and aggregate economic activities in the short and long runs. First, we show that in an economy where financial market has not developed, raising minimum capital requirements improves resource allocation and welfare in the long run, while it reduces welfare in an economy where financial market has developed. Second, our study reveals that an economy with a minimum capital adequacy ratio of 8% has a larger drop in aggregate net worth, consumption, and output when a negative capital quality shock occurs. However, during the financial crisis, the economy recovers faster than an economy with a higher minimum capital ratio (about 10%). These results indicate that tighter bank requirements temporally mitigate crises in economies with a developed financial market; however, they do not promote their activity in the long run.
Keywords: E44; G21; G28; O11; O16; 330; Minimum Capital Requirements; Financial Development; Macroeconomic Analyses